Utilization Strategy and Management of Green Waste to Improve Wasteland Fertility in Australia - Shekhada, Divyesh (International Journal of Environment, Agriculture and Biotechnology, 2019)
This paper covers production of food waste in Australia, including to find the best solution to address the food waste issue by collective understanding of what we mean by food waste and where it happens. Recognizing what we are starting at now do well can empower us to take in and use from prevailing exercises and moreover development. Moreover, the point of administration and recycling of food waste in header of biomass preparation can build soil fertility of wasteland in Australia. With the aim of considering natural composts are infinite, biodegradable, reasonable, and ecologically attractive. This thought can be proposed as reusing of waste as a natural fertilizer to enhance soil readiness of wasteland in Australia.